The Influence of Green Marketing on the Revenues and Firm Value of Companies in Asia - Diwa Artha Ramadhany; Dwi Nita Ariyani; Mayank Kumar Pandey; Rudresh Pandey; Padmalini Singh; Maulana Hanif; Bhavishya Bhavishya; Madhumita Kumari (Asia Pacific Journal of Management and Education (APJME), 2024)
Green marketing is a marketing and product development method from a company oriented towards environmental sustainability. This research further aims to discover if green marketing can influence the increase in revenue and firm value of companies in Asia through the ROA ROE and PER indicators. In its analysis, this research uses a research methodology in the form of quantitative research with a research sample of 30 companies in Asia that implement green marketing with indicators (Green product, green promotion, green price and green place) and then tested using SPSS. The results of this research are 1. Green marketing turns out to have no correlation with increasing company revenue in Asia 2. Green marketing has an influence on firm value. The implications of this research encourage companies in Asia to focus more on green marketing strategies as a way to increase their long-term value, which may be more important than short-term revenue growth for increasing a company's stability and future growth.